2017
DOI: 10.1017/s0031182017000786
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the spatial distribution of Fasciola hepatica in bovines using decision tree, logistic regression and GIS query approaches for Brazil

Abstract: Fascioliasis is a condition caused by the trematode Fasciola hepatica. In this paper, the spatial distribution of F. hepatica in bovines in Brazil was modelled using a decision tree approach and a logistic regression, combined with a geographic information system (GIS) query. In the decision tree and the logistic model, isothermality had the strongest influence on disease prevalence. Also, the 50-year average precipitation in the warmest quarter of the year was included as a risk factor, having a negative infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
(30 reference statements)
0
20
0
1
Order By: Relevance
“…The International Panel on Climate Change (CLINE, 2007) reported that countries in Latin America may observe an increase in disease incidence, due to the increase of inundation and specific vectors. Therefore, the increase in temperature and precipitation will change the prevalence of fascioliasis, as was also determined in Brazil by Bennema et al (2017) and Dutra et al (2010). Silva et al (2016) noted that La Nina years affected bovine fascioliasis (temperature and rainfall).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The International Panel on Climate Change (CLINE, 2007) reported that countries in Latin America may observe an increase in disease incidence, due to the increase of inundation and specific vectors. Therefore, the increase in temperature and precipitation will change the prevalence of fascioliasis, as was also determined in Brazil by Bennema et al (2017) and Dutra et al (2010). Silva et al (2016) noted that La Nina years affected bovine fascioliasis (temperature and rainfall).…”
Section: Discussionmentioning
confidence: 78%
“…In cattle, previous studies have also shown that the prevalence of fascioliasis was mainly in the southern states (ALEIXO et al, 2015;DUTRA et al, 2010;SILVA et al, 2016), with an economic loss of approximately US$ 210 million/year (MOLENTO et al, 2018). Bennema et al (2017) have also determined that the best suitability area for F. hepatica development, based on a range of isothermality data was the south region of the country. Other studies have also investigated the climate effects and surveillance data for fascioliasis in Europe (CAMINADE et al, 2015;NOVOBILSKÝ et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease may cause production losses of US$90-210 million annually (Rahmeto et al, 2010;Molento et al, 2018), and Dutra et al (2010) reported that F. hepatica is endemic in Rio Grande do Sul (RS), a state located in the south of Brazil, with an average prevalence of 14.3%. The distribution of F. hepatica in Brazil is extensive in the southern region and its presence reaches up to the south border of the Amazon region (Bennema et al, 2014(Bennema et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%